Metagenome-wide analysis of antibiotic resistance genes in a large cohort of human gut microbiota - Hu, Yongfei; Yang, Xi; Qin, Junjie; Lu, Na; Cheng, Gong; Wu, Na; Pan, Yuanlong; Li, Jing; Zhu, Liying; Wang, Xin; Meng, Zhiqi; Zhao, Fangqing; et al. (Nature communications, 2013)
The human gut microbiota is a reservoir of antibiotic resistance genes, but little is known about their diversity and richness within the gut. Here we analyse the antibiotic resistance genes of gut microbiota from 162 individuals. We identify a total of 1,093 antibiotic resistance genes and find that Chinese individuals harbour the highest number and abundance of antibiotic resistance genes, followed by Danish and Spanish individuals. Single-nucleotide polymorphism-based analysis indicates that antibiotic resistance genes from the two European populations are more closely related while the Chinese ones are clustered separately. We also confirm high abundance of tetracycline resistance genes with this large cohort study. Our study provides a broad view of antibiotic resistance genes in the human gut microbiota. The appearance of antibiotic resistance has been attributed to the misuse of antibiotics. By analysing the diversity of antibiotic resistance genes present in 162 human gut microbiota samples, the authors find that Chinese individuals harbour a larger pool of resistance genes than Spanish or Danish counterparts.